The effect of reminiscence therapy to reduce loneness in elderly - Sahmin, Ifing Puji; Abdullah, Sri Muliati (Insight: Jurnal Ilmiah Psikologi, 2024)
This study investigates the impact of reminiscence therapy on reducing loneliness among the elderly. The research involved five participants who scored high to medium on loneliness assessments, specifically in the experimental group. Subjects for this group were chosen using a random assignment technique. The study employed a one-group pre-test and post-test design. The data collection tools used in this study included the UCLA Loneliness Scale (3-item version), observations, and interviews. For data analysis, the Wilcoxon Rank Test was employed to assess differences in loneliness scores in the experimental group before and after receiving reminiscence therapy. The results indicated a significant difference in loneliness scores, with a Z value of -2.060 and a p value of 0.039. This finding suggests that reminiscence therapy effectively reduces loneliness among the elderly. Keywords: Reminiscence therapy, loneliness, ederly.